Measurement of D0-D[bar]0 mixing and CP violation in two-body D0 decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We present a measurement of D0−¯¯¯D0 mixing and CP violation using the ratio of lifetimes simultaneously extracted from a sample of D0 mesons produced through the flavor-tagged process D*+→D0π+, where D0 decays to K∓π±, K−K+, or π−π+, along with the untagged decays D0→K∓π± and D0→K−K+. The lifetimes of the CP-even, Cabibbo-suppressed modes K−K+ and π−π+ are compared to that of the CP-mixed mode K∓π± in order to measure yCP and ΔY. We obtain yCP=[0.72±0.18(stat)±0.12(syst)]% and ΔY=[0.09±0.26(stat)±0.06(syst)]%, where ΔY constrains possible CP violation. The yCP result excludes the null mixing hypothesis at 3.3σ significance. This analysis is based on an integrated luminosity of 468 fb−1 collected with the BABAR detector at the PEP-II asymmetric-energy e+e− collider.
Im Titel ist die Zahl "0" hochgestellt
Im Titel hat das zweite "D" von "D0" einen Oberstrich
Gesehen am 10.11.2021